Prediction of quadriceps one repetition maximum (1RM) among novice lifters using 1RM equations/ Aini Najihah Nasarudin, Fatin Fazira Sidek, Ida Hasni Shaari - Nasarudin, Aini Najihah; Sidek, Fatin Fazira; Shaari, Ida Hasni (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Objectives: To determine the accuracy of one Repetition Maximum (1-RM) equations in identifying 1RM for quadriceps muscle among novice lifters. Methodology:This is an experimental research study. A total of 60 female university students of with mean age 21.6 ± 1.77 years old participated in the study. Random load from the quadriceps bench was placed on the participant's lower leg. The weight is continuously added until the subjects were unable to lift their leg through full knee extension or complain of fatigue. The last weight lifted was recorded as the participant's 1RM load. After 48 hours, the second session was conducted. Participants were given weight at 50% from their 1RM weight and performed as many repetitions of knee extension. The subject's predicted 1RM was calculated using Brizicky and Epley equations. Results: The mean load identified through the actual 1RM testing method (3.18 ±1.38) was found to be higher than equations (Epley: 2.13 ± 1.12) / (Brzycki: 2.62 ± 1.75) calculation. The Bland-Altman plot indicates that SD agreement between actual 1RM - Epley equation fall between SD ± 1.96 with a high value of 2.12 and a low value at -0.26. For the actual 1RM- Brzycki, the SD agreement falls between SD ± 1.96 with a high value of 3.1 and low value at (-) 2.0. Conclusion: Both Epley and Brizicky equations have underestimated the 1RM for quadriceps muscle among novice lifters by 1.05 kg (Epley equation) and 0.5 kg (Brzycki equation), respecctively.